Comparison of average global exposure of population induced by a macro 3G network in different geographical areas in France and Serbia. Issue 6 (6th July 2016) - Huang, Yuanyuan; Varsier, Nadège; Niksic, Stevan; Kocan, Enis; Pejanovic‐Djurisic, Milica; Popovic, Milica; Koprivica, Mladen; Neskovic, Aleksandar; Milinkovic, Jelena; Gati, Azeddine; Person, Christian; Wiart, Joe
Abstract : This article is the first thorough study of average population exposure to third generation network (3G)‐induced electromagnetic fields (EMFs), from both uplink and downlink radio emissions in different countries, geographical areas, and for different wireless device usages. Indeed, previous publications in the framework of exposure to EMFs generally focused on individual exposure coming from either personal devices or base stations. Results, derived from device usage statistics collected in France and Serbia, show a strong heterogeneity of exposure, both in time, that is, the traffic distribution over 24 h was found highly variable, and space, that is, the exposure to 3G networks in France was found to be roughly two times higher than in Serbia. Such heterogeneity is further explained based on real data and network architecture. Among those results, authors show that, contrary to popular belief, exposure to 3G EMFs is dominated by uplink radio emissions, resulting from voice and data traffic, and average population EMF exposure differs from one geographical area to another, as well as from one country to another, due to the different cellular network architectures and variability of mobile usage. Bioelectromagnetics. 37:382–390, 2016. © 2016 Wiley Periodicals, Inc.